Sistem Syarikah Abdan dalam Fikih Islam dan Contoh Penerapannya pada Era Kontemporer - Rahmat, Rahmat; Ningsih, Fitriah (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
Syarikah al-abdan is a form of muamalah that can be applied today in improving the welfare of the people. However, in practice today, it seems that there are problems among Muslims in seeing and sorting out the practice of syarikah al-abdan which is following the Shari'a. For this reason, the purpose of this study is to describe the syarikah al-abdan scheme and its current contemporary application forms. The research method used is a qualitative descriptive research approach with library research techniques and content analysis. The results of this study indicate that syarikah al-abdan is a form of business cooperation between two or more people preceded by mutual agreement in determining the results of the profits and/or wages between them. However, in its implementation, it is necessary to pay attention to the pillars and requirements of the syarikah al-abdan, and to consider the views of the majority of madhhab scholars and the Indonesian Ulama Council (MUI). In practice, this study describes the form of syarikah al-abdan in the profession of fisherman and tailor.